2003
DOI: 10.1073/pnas.1434337100
|View full text |Cite
|
Sign up to set email alerts
|

Semipermeable species boundaries betweenAnopheles gambiaeandAnopheles arabiensis: Evidence from multilocus DNA sequence variation

Abstract: Attempts to reconstruct the phylogenetic history of the Anopheles gambiae cryptic species complex have yielded strongly conflicting results. In particular, An. gambiae, the primary African malaria vector, is variously placed as a sister taxon to either Anopheles arabiensis or Anopheles merus. The recent divergence times for members of this complex complicate phylogenetic analysis, making it difficult to unambiguously implicate interspecific gene flow, versus retained ancestral polymorphism, as the source of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
196
3
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(215 citation statements)
references
References 31 publications
14
196
3
2
Order By: Relevance
“…Additionally mosquitoes often exist rather as closely related species complexes that, when studied intimately -as with the Anopheles gambiae complex in Africa -can be observed to be diverging at some parts of the genome under low recombination while other parts of the genome undergo gene flow (Besansky et al 2003;Reidenbach et al 2012). Do we split these into separate species or group them into one?…”
Section: O S Q U I T O S P E C I E S a S A T A X O N O M I C U N I Tmentioning
confidence: 99%
“…Additionally mosquitoes often exist rather as closely related species complexes that, when studied intimately -as with the Anopheles gambiae complex in Africa -can be observed to be diverging at some parts of the genome under low recombination while other parts of the genome undergo gene flow (Besansky et al 2003;Reidenbach et al 2012). Do we split these into separate species or group them into one?…”
Section: O S Q U I T O S P E C I E S a S A T A X O N O M I C U N I Tmentioning
confidence: 99%
“…An investigation of DNA sequence variation in four gene loci (one from each of chromosomes X and 2 and two from chromosome 3) sampled from multiple specimens shows considerable similarity of gene polymorphisms and even haplotypes between the two autosomal chromosomes of A. gambiae and A. arabiensis (48), which share polymorphic inversions. At the X chromosome locus, however, there are fixed nucleotide differences and greater overall nucleotide differentiation between A. gambiae and A. arabiensis.…”
Section: Speciation In Malaria's Mosquitoesmentioning
confidence: 99%
“…Nevertheless, comparison of allopatric and sympatric populations suggests locale-specific unidirectional introgression from A. arabiensis into A. gambiae. Indeed, the acquisition by A. gambiae of alleles from the more arid-adapted A. arabiensis may have contributed to its spread and ecological dominance (48). A more definitive test of the suppressed-recombination model of chromosomal speciation would call for estimation of the K A ͞K S ratio in 20 or more genes distributed among the three chromosomes of these two species, as well as among the other five species and additional incipient species.…”
Section: Speciation In Malaria's Mosquitoesmentioning
confidence: 99%
“…These results may suggest a possible introgression event (Tang et al, 1996), which was not revealed by mtDNA. Whereas the Malaysian Borneo clade remained isolated, a genetic admixture with unequal nuclear and mitochondrial gene flow during coexistence of the two lineages is suggested for the Continental and Indonesian clades (della Torre et al, 1997;Garcia-Paris et al, 2003;Gentile et al, 2002;Besansky et al, 2003).…”
Section: Mtdna Versus Its2mentioning
confidence: 99%